Feminine Spiritual Hermeneutics In Easter Egg and Maulid Egg; A Comparative Elaboration - Syamsul Asri (Universitas Islam Negeri Alauddin Makassar, 2018)
The main focus of this paper,comparative elaboration of Easter egg in Orthodox Christianity in Eastern Europe and Maulid egg in southern Sulawesi, become the strategic field of female engagement with their communality. The very crucial element in this brief comparison is the obvious feminine quality of both Maulid egg and Easter egg, thus both of this socio-religious practices conducted, exercised, examined by female subjects in its primer state. I construct the feminine role in Maulid egg and Easter egg through three centripetal stages in which feminine subject articulate its self-definition and self-positioning in socio-religious landscape; garden, kitchen, and public ritual occupying public sphere, all of which reflect the strategic and irreversible role and self-articulation by feminine subjects.